1987
DOI: 10.1007/bf00128424
|View full text |Cite
|
Sign up to set email alerts
|

A repertory grid study of staff and students' personal constructs of educational research

Abstract: This case study discusses some staff and students' personal constructs of research effectiveness. A repertory grid form (Kelly, 1955) and associated computer programs (Shaw, 1980) were used as alternative instruments to the traditional questionnaire for evaluating the criteria for effective research held by six university staff and six postgraduate students. The results are reported and it is suggested that the repertory grid technique is a powerful heuristic tool in higher education to aid people in construin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…To form the Q sample, sixteen teacher educators from three different universities in Sweden were interviewed (see also Lundström et al, 2019). The interviews were conducted with the Repertory Grid Technique (RGT) (see Kelly, 1955;Zuber-Skerritt, 1987). The aim of using this technique is to elicit underlying, or tacit, criteria for assessment (Björklund, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…To form the Q sample, sixteen teacher educators from three different universities in Sweden were interviewed (see also Lundström et al, 2019). The interviews were conducted with the Repertory Grid Technique (RGT) (see Kelly, 1955;Zuber-Skerritt, 1987). The aim of using this technique is to elicit underlying, or tacit, criteria for assessment (Björklund, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…A review of recent studies found that the repertory grid has been used to promote active learner engagement (Pope, 1982), to foster intrinsic motivation for learning mathematics (Middleton, 1995), to probe perceived attributes of the “ideal teacher” (Kozikoglu, 2017), and elucidate principals’ conceptions of the “ideal principal” (Bektas, 2014). Among undergraduates, PCT has been used to explore similarities among students’ and professors’ conceptual knowledge of science (Kreber et al, 2003), to promote mastery of research methodologies (Hamid, Stapa, Mustafa, & Hashim, 2012; Zuber-Skerrittt, 1987), and to construe the creativity of college professors (de Sousa, 2007). Researchers have adopted PCT to study students’ aesthetic responses to musical compositions (Gilbert, 1990) and secondary school teachers’ perceptions of music students (Hewitt, 2005).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Dağarcık ağı nitel ve nicel bilgiyi bir arada içerir. Yapı ve elementlerin oluşturulması nitel bilgiyle sağlanırken element ve yapılar arasındaki ilişkiler nicel olarak değerlendirilir (Bell, 2003;McQualter, 1986;Zuber-Skerrit, 1987). Dağarcık ağı Kelly (1955Kelly ( , 1991 tarafından bireylerin, bizzat içerisinde oldukları ortamlarda etkileşimde bulunduğu insanları düşünerek o insanları tanımlayan sözcükler aracılığıyla ana bilişsel kurgularını belirlemeyi amaçlayan bir tekniktir.…”
Section: İşlemunclassified